AKUNTABILITAS KOPERASI MELALUI LAPORAN KEUANGAN - Bq. Anggun Hilendri (Jurnal Aplikasi Akuntansi, 2018)
Cooperatives are one of three types of business entities that support the Indonesian economy in addition to State-Owned Enterprises (BUMN) and Private-Owned Enterprises (BUMS). The development and growth of cooperatives in Indonesia is endeavored to continue to synergize with the duties of cooperatives in holding their institutions accountable to the government and the development of their business to their members. This is a form of implementation of cooperative accountability in which cooperatives must be able to manage services and be informed to interested parties in the form of financial statements. The purpose of this study was to find out how the accountability of Karya Mandiri Selong cooperatives through cooperative financial statements that have been prepared. Accountability of Karya Mandiri Selong cooperatives through the preparation of financial reports is not optimal as indicated by the preparation of financial statements in the form of monthly reports containing reports on loans or accounts receivable and deposits from cooperative customers. This is because the management's understanding of financial accounting standards is still lacking. The hope is for the future Karya Mandiri Selong cooperatives can compile financial reports in accordance with financial accounting standards so that accountability is maintained and member trust increases.